The current status of the elemental defense hypothesis in relation to pathogens - Hoerger, Anja C.; Fones, Helen N.; Preston, Gail (Frontiers in Plant Science, 2013)
Metal hyperaccumulating plants are able to accumulate exceptionally high concentrations of metals, such as zinc, nickel, or cadmium, in their aerial tissues. These metals reach concentrations that would be toxic to most other plant species. This trait has evolved multiple times independently in the plant kingdom. Recent studies have provided new insight into the ecological and evolutionary significance of this trait, by showing that some metal hyperaccumulating plants can use high concentrations of accumulated metals to defend themselves against attack by pathogenic microorganisms and herbivores. Here, we review the evidence that metal hyperaccumulation acts as a defensive trait in plants, with particular emphasis on plant-pathogen interactions. We discuss the mechanisms by which defense against pathogens might have driven the evolution of metal hyperaccumulation, including the interaction of this trait with other forms of defense. In particular, we consider how physiological adaptations and fitness costs associated with metal hyperaccumulation could have resulted in trade-offs between metal hyperaccumulation and other defenses. Drawing on current understanding of the population ecology of metal hyperaccumulator plants, we consider the conditions that might have been necessary for metal hyperaccumulation to be selected as a defensive trait, and discuss the likelihood that these were fulfilled. Based on these conditions, we propose a possible scenario for the evolution of metal hyperaccumulation, in which selective pressure for resistance to pathogens or herbivores, combined with gene flow from non-metallicolous populations, increases the likelihood that the metal hyperaccumulating trait becomes established in plant populations.